Strategies for Reducing Induced Demand in Hospitals Affiliated with Iran University of Medical Sciences: A Qualitative Study - Hesam Seyedin; Mahnaz Afshari; Parvaneh Isfahani; Ebrahim Hasanzadeh; Maryam Radinmanesh; Rasoul Corani Bahador (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Induced demand is a major challenge for health systems worldwide. It increases costs, especially for patients. The purpose of this study is to identify strategies for reducing induced demand for health care in hospitals affiliated with the Iran University of Medical Sciences (IUMS). Methods: This was a qualitative study conducted in 2018. The authors conducted in-depth, semi-structured interviews with 20 participants, including IUMS faculty members, physicians, public hospital managers, patients, and researchers with academic and practical experience. Inductive content analysis was used to analyze data. Data analysis was performed in MAXQDA10. Results: Overall,  the authors extracted 24 subthemes from the interviews and classified them into the health system, insurer, healthcare provider, and healthcare recipient. They are key factors regarding the induced demand for healthcare in the public hospitals under study. Conclusion: Reducing induced demand for healthcare requires concerted actions by health policymakers and managers at the level of the health system, insurers, healthcare providers, and healthcare recipients. Therefore, policymakers and managers of the health system should take appropriate measures such as the development of guidelines and protocols by different departments, especially the emergency department, classification (primary, secondary, and tertiary care), and referral system. They expand the monitoring role of insurance companies (transforming the payment system into the global diagnosis-related group)  to reduce the induced demand for health.